Influenza A virus replication has a stronger dependency on Raf/MEK/ERK signaling pathway activity than SARS-CoV-2 - Hoffmann, Helen; Ebensperger, Marina; Schönsiegel, Annika; Hamza, Hazem; Koch-Heier, Julia; Schreiber, André; Ludwig, Stephan; Schindler, Michael; Planz, Oliver (Frontiers in Cellular and Infection Microbiology, 2023)
The recent COVID-19 pandemic again highlighted the urgent need for broad-spectrum antivirals, both for therapeutic use in acute viral infection as well as pandemic preparedness in general. The targeting of host cell factors hijacked by viruses during their replication cycle presents one possible strategy for development of broad-spectrum antivirals. By inhibiting the Raf/MEK/ERK signaling pathway, a central kinase cascade of eukaryotic cells, which is being exploited by numerous viruses of different virus phyla, the small molecule MEK inhibitor zapnometinib has the potential to address this need. With a drug targeting a host cell kinase, one might expect the drug's EC50 to be independent of the virus. But recent experiments using zapnometinib against SARS-CoV-2 and IAV suggest otherwise. We here performed a side-by-side comparison of the antiviral efficacy of zapnometinib against IAV and SARS-CoV-2 determining the concentration leading to 50% of its effect on the virus (EC50) and the concentration leading to 50% reduction of ERK phosphorylation (IC50) value in a comparable manner, using the same experimental conditions. Our results show that the EC50 and IC50 value of zapnometinib are indeed lower for IAV compared to SARS-CoV-2 using one representative strain for each. The results indicate suggest that IAV's replication has a stronger dependency on an active Raf/MEK/ERK pathway and thus that IAV is more susceptible to treatment with zapnometinib than SARS-CoV-2. With zapnometinib's favorable outcome in a recent phase II clinical trial in hospitalized COVID-19 patients the present results are even more promising for an upcoming phase II clinical trial in severe influenza virus infection.